Pengkajian Teknis Operasional Pesawat Tua Di Indonesia - Sudjono, Idjon (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
T7te usage of aging aircraft is nwre widespread in deueloping countries such as Eastern Europe,Africa, LJ:ztin America and central Anzerim and Indonesia. T7ze reason is that tltere is an interestingoffer of cooperation from big companies wlw want to pluzse out its fleet of aging aircraft as well as inthe 1990s when Lutftuznsa offered offset to IPTN as pm;o!f tlte purchase of 23 8737-200 aircraft.Actually operating tlte aircraft B-737-200 should be installed Huskit to meet new regulations. Huskitinstallation cost approximately US 1 million per machine unit. So for tlte type of B-737 series 200twin-engine will cost US 2 million per aircraft unit, not including losses from loss of use Huskitinstallation ti1ne.Until now, in Indonesia is still operated type of aging aircraft such as B-700-200, MD-80, MD-82and MD-90. In this study will put forward the constraints for operations and procurement of agingaircraft.Keywords: aging aircraft, maintenance